AKTIVITAS ANTIOKSIDAN EKSTRAK LAMUN (Enhalus acoroides) ASAL PULAU LAE-LAE MAKASSAR TERHADAP RADIKAL ABTS - Fitriyanti Jumaetri Sami; Syamsu Nur; Amriani Sapra; Libertin Libertin (Politeknik Kesehatan Makassar, 2020)
Antioxidants are compounds that can inhibit or prevent oxidation reactions, which are the result of chemical reactions and metabolic processes that occur in the body. Enhalus acoroides is a type of seagrass found in Indonesian waters, generally living in sandy sediments with high bioturbation. Lamun has good nutrition and fiber so that it can be a source of food and medicine. The aim of this study was to examine the antioxidant activity of the seagrass extract Enhalus acoroides against ABTS radicals (2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid). The results of the study of seagrass extract using ethanol solvents had a very strong antioxidant category ie 38,008 µg /ml, the smaller the absorbance value, the higher the inhibitory value in which the antioxidant activity of the extract is higher, but when compared with the routine compound control of 0.500 µg /ml, seagrass ethanol extract is still lower.